Design and operation of power systems with large amounts of wind power : Final report, Phase one 2006-08, IEA WIND Task 25 - Holttinen, Hannele (2013)
There are already several power systems coping with large amounts of wind power. High penetration of wind power has impacts that have to be managed through proper plant interconnection, integration, transmission planning, and system and market operations. This report is a summary of case studies addressing concerns about the impact of wind power s variability and uncertainty on power system reliability and costs. The case studies summarized in this report are not easy to compare due to different methodology and data used, as well as different assumptions on the interconnection capacity available. Integration costs of wind power need to be compared to something, like the production costs or market value of wind power, or integration cost of other production forms. There is also benefit when adding wind power to power systems: it reduces the total operating costs and emissions as wind replaces fossil fuels. Several issues that impact on the amount of wind power that can be integrated have been identified. Large balancing areas and aggregation benefits of large areas help in reducing the variability and forecast errors of wind power as well as help in pooling more cost effective balancing resources. System operation and working electricity markets at less than day-ahead time scales help reduce forecast errors of wind power. Transmission is the key to aggregation benefits,electricity markets and larger balancing areas. From the investigated studies it follows that at wind penetrations of up to 20 % of gross demand (energy), system operating cost increases arising from wind variability and uncertainty amounted to about 1 4 /MWh. This is 10 % or less of the wholesale value of the wind energy.